Application of Multiple Line Integrated Spectroscopy on CO Concentration Measurement - Komada, P.; Cieszczyk, S. (Elektronika ir Elektrotechnika, 2013)
The paper presents possibility of application multiple of integrated spectroscopy for measuring CO concentration in a gas mixture. Sensors that are based on the method discussed can be applied in analyses of gas mixtures inside a power boiler or products of biomass gasification process. The principles of the method has been presented, however the main attention was paid to proper selection of the wavelength range and thus optoelectronic components. It would limit influence of disturbance factors and on the other hand, enable higher dynamic range of the CO analyser. Both simulation and laboratory tests that were presented in the paper would enable to build CO analyser that could operate in industrial conditions at acceptable measurement uncertainty. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5648